Multimodal Transportation Policy to Address The High Cost of Goods in 3T Regions (Lagging, Frontier, and Outer): Bibliometric Analysis and Future Research Agenda (Case Study of Papua) - Nikolas Makanuay; Rifqi Raza Bunahri; Musri Kona; Dhian Supardam; Hadi Prayitno (Dinasti International Journal of Education Management And Social Science, 2023)
This study discusses the implementation of multimodal transportation policies in Papua, as an effort to address the high cost of goods in the region with the aim of reducing logistics costs and accelerating economic growth. Shipping rates in Indonesia remain an unresolved issue, especially in the Papua region, classified as a 3T area (lagging, frontier, and outer), leading to high commodity prices. The research employs bibliometric analysis using the Scopus database as its data source. Out of a total of 5,930 articles found, a filtering process considering location, keywords, and a time range from 2009 to 2023 was conducted. As a result, 200 relevant articles were identified for analysis, and from this pool, 15 articles most aligned with relevant keywords were selected as the primary references for this study. The research findings indicate that the implementation of multimodal transportation policies in Papua has successfully reduced price disparities and improved accessibility to mountainous regions. However, challenges persist in the development of multimodal transportation in 3T areas, prompting recommendations for policies such as collaboration and logistics integration across modes, seaplane transportation, and mountain flying training to optimize logistics delivery in mountainous areas. Additionally, the use of unmanned aerial vehicles (drones) for more efficient logistics delivery is suggested. Furthermore, future research should focus on various aspects of multimodal transportation, including ride-sharing, mobility as a service, railway transportation, traffic congestion, land use, climate change, greenhouse gas emissions, traffic control, transportation costs, safety, travel time, social welfare, and expenses. This study provides insights into the positive impact of multimodal transportation policies in Papua and offers guidance for future development to address the issue of high commodity prices in 3T regions.